How to live, or, A life of Montaigne in one question and twenty attempts at an answer - Bakewell, Sarah (Other Press, 2010)
This book, a spirited and singular biography, relates the story of Montaigne's life by way of the questions he posed and the answers he explored. It traces his bizarre upbringing, youthful career and sexual adventures, his travels, and his friendships with the scholar and poet Étienne de La Boétie and with his adopted “daughter,” Marie de Gournay. And we also meet his readers, who for centuries have found in Montaigne an inexhaustible source of answers to the haunting question, “How to live?”